Membangun Kesatuan dalam Keberagaman: Edukasi Toleransi dan Keadilan dalam Beragama - Aditya Rionaldy Danarghani; Muhammad Rafli Adi Nugroho; Nathan Herliawan; Nicholas Gareth Adikusumo; Vicky Winata Phan; Aryusmar; Heru Widoyo (PT. AHLAL PUBLISHER NUSANTARA, 2025)
Indonesia is a multicultural nation whose extensive diversity must be managed wisely to preserve national unity and prevent the rise of intolerance among young generations. This project aims to strengthen unity in diversity by promoting tolerance, justice, and inclusive religious education through Character Building activities aligned with SDG 16, which emphasizes peace, justice, and strong institutions. Using a qualitative research method involving field observations, semi-structured interviews, and educational socialization sessions, the study reveals that interreligious relations within the local community are generally harmonious, upheld by mutual respect, collaborative activities, and conflict resolution based on dialogue. Nevertheless, minor tensions still emerge among students, typically triggered by insensitive jokes or misunderstandings related to religious identity. The educational program successfully enhanced students’ awareness of the importance of tolerant behavior, fairness in social interactions, and appreciation of cultural and religious diversity. The findings underscore that inclusive religious education plays a crucial role in shaping young people as peace agents who uphold unity, resist intolerance, and contribute to the creation of a just, peaceful, and harmonious society. Keywords: Unity, Diversity, Education, Tolerance, Justice Abstrak Indonesia merupakan negara multikultural dengan keberagaman agama, budaya, dan etnis yang perlu dikelola secara bijak untuk menjaga kesatuan bangsa serta mencegah munculnya sikap intoleransi, terutama di kalangan generasi muda. Proyek ini bertujuan memperkuat kesatuan dalam keberagaman melalui edukasi toleransi, keadilan, dan nilai-nilai inklusif dalam kegiatan Character Building yang sejalan dengan SDGs poin 16 mengenai perdamaian, keadilan, dan institusi yang kuat. Menggunakan metode penelitian kualitatif melalui observasi lapangan, wawancara, serta kegiatan sosialisasi edukatif, penelitian menemukan bahwa hubungan antarumat beragama di masyarakat pada umumnya harmonis berkat sikap saling menghargai, kerja sama lintas agama, serta penyelesaian konflik yang mengutamakan dialog. Namun demikian, konflik kecil masih terjadi di kalangan siswa, biasanya dipicu oleh candaan sensitif atau kesalahpahaman terkait identitas agama. Program edukasi yang dilaksanakan mampu meningkatkan pemahaman siswa mengenai pentingnya bersikap toleran, berperilaku adil dalam kehidupan sehari-hari, serta menghargai keberagaman sebagai kekuatan. Penelitian ini menegaskan bahwa pendidikan agama yang inklusif berperan penting dalam membentuk generasi muda sebagai agen perdamaian yang menjunjung kesatuan dan berkontribusi pada terciptanya masyarakat yang adil, damai, dan harmonis. Kata kunci: Kesatuan, Keberagaman, Edukasi, Toleransi, Keadilan